The Effect of Online Learning Towards Learning Motivation of University Students on Social Student Course - Nurhikmah Nurhikmah; Dholina Inang Pambudi; Ali Mustadi (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to determine the effect of online learning toward the learning motivation of Elementary School Teacher Education (PGSD) students in social studies learning.  The research approach used is quantitative research, ex post facto type.  The research population was 316 students at Primary School Teacher Education (PGSD) at Ahmad Dahlan University, Yogyakarta. The research sample was 118 students. Data obtained through interviews and questionnaires.  The data obtained from the questionnaire were analyzed using descriptive statistics and inferential analysis.  The results of the regression test with a simple linear test showed a sig value of 0.827, with the criteria Sigα (0.05) this means that there is no effect of variable X (online learning) on variable Y (learning motivation). Thus, this study concludes that there is no significant negative effect of online learning on students' learning motivation. Of the four indicators of learning motivation, namely a sense of responsibility, enthusiasm, independence, and belief, they are in the very good category.  During the teaching and learning process, most of the students were enthusiastic about participating in lectures and flexible learning.  Through online learning, there are many positive things that can be felt to be able to increase the spirit of learning, such as more flexible learning, not being hindered by distance and time and being able to train students' learning independence.